2020
DOI: 10.2196/19347
|View full text |Cite
|
Sign up to set email alerts
|

Flattening the Mental Health Curve: COVID-19 Stay-at-Home Orders Are Associated With Alterations in Mental Health Search Behavior in the United States

Abstract: Background The coronavirus disease (COVID-19) has led to dramatic changes worldwide in people’s everyday lives. To combat the pandemic, many governments have implemented social distancing, quarantine, and stay-at-home orders. There is limited research on the impact of such extreme measures on mental health. Objective The goal of this study was to examine whether stay-at-home orders produced differential changes in mental health symptoms using internet s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
127
3
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(148 citation statements)
references
References 26 publications
(34 reference statements)
15
127
3
3
Order By: Relevance
“…2Additionally, personal exposure (e.g., self or close other tested positive to COVID-19) was associated with higher acute stress and depressive symptoms, whereas community-level exposures (e.g., stay-at-home orders) were not, suggesting that concerns about contracting the disease outweighed concerns about pandemic-related disruptions in daily life. Unlike big data findings suggesting that stay-at-home orders may "flatten the curve" of psychological symptoms (e.g., anxiety, hopelessness, suicide) in the U.S., (18) our findings offer evidence that respondents' acute stress and depressive symptoms continued rising after the stay-at-home orders were implemented. Furthermore, our data suggest that individuals who continued working during this early phase of the pandemic were less depressed than individuals who were not working, even though they were at greater risk for contracting the virus.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…2Additionally, personal exposure (e.g., self or close other tested positive to COVID-19) was associated with higher acute stress and depressive symptoms, whereas community-level exposures (e.g., stay-at-home orders) were not, suggesting that concerns about contracting the disease outweighed concerns about pandemic-related disruptions in daily life. Unlike big data findings suggesting that stay-at-home orders may "flatten the curve" of psychological symptoms (e.g., anxiety, hopelessness, suicide) in the U.S., (18) our findings offer evidence that respondents' acute stress and depressive symptoms continued rising after the stay-at-home orders were implemented. Furthermore, our data suggest that individuals who continued working during this early phase of the pandemic were less depressed than individuals who were not working, even though they were at greater risk for contracting the virus.…”
Section: Discussioncontrasting
confidence: 89%
“…(17) However, analysis of Goog-leTrends data suggests that stay-at-home orders may have flattened rising distress as the number of distress-related searches in the U.S. plateaued soon after the lockdowns began. (18) At present, little is known about the relative impact of these various exposures-direct, media-driven, or community wide -on individuals' early pandemic-related psychological responses. Understanding the risk and protective factors affecting public response is critical to promoting community resilience as countries across the globe face a surge of new COVID-19 infections.…”
Section: Introductionmentioning
confidence: 99%
“…We did observe decreases in anxiety and depression that paralleled the typical post–final examination drop, which suggests some resilience in the face of COVID-19; however, the overall values remained elevated above those observed during typical academic breaks. This may also be consistent with the adjustment period to the rapidly changing landscape of social media, policies, and media coverage [ 25 ].…”
Section: Discussionsupporting
confidence: 68%
“…Despite the fact that during the Measures period the temperature was warmer and there was more sunshine than usual, the analysis on weather data for Germany did not show a significant impact on the changed mental health symptoms. Our findings are supported by a growing body of evidence from ongoing studies [49] and recently published research [50], as well as anecdotal evidence reported in various mainstream media reports [51][52][53] which suggest that at least in the short-term the mental health effects of the COVID-19 measures may not be as negative as expected. One factor may be that the stress of everyday life and work/study is reduced during lockdown and home office/schooling.…”
Section: Principal Resultssupporting
confidence: 88%